A lie for a lie - Hunting, Helena (Montlake Romance, 2019)
Sometimes I need an escape from the demands, the puck bunnies, and the notoriety that come with being an NHL team captain. I just want to be a normal guy for a few weeks. So when I leave Chicago for some peace and quiet, the last thing I expect is for a gorgeous woman to literally fall into my lap on a flight to Alaska. Even better, she has absolutely no idea who I am. Lainey is the perfect escape from my life. My plan for seclusion becomes a monthlong sex fest punctuated with domestic bliss. But it ends just as abruptly as it began. When I<U+2019>m called away on a family emergency, I realize too late that I have no way to contact Lainey. A year later, a chance encounter throws Lainey and me together again. But I still have a lie hanging over my head, and Lainey<U+2019>s keeping secrets of her own. With more than lust at stake, the truth may be our game changer.